HALL EFFECT CONTROLLED GAS DYNAMICS IN PROTOPLANETARY DISKS. II. FULL 3D SIMULATIONS TOWARD THE OUTER DISK - Bai, Xue-Ning (The Astrophysical journal, 2015)
We perform three-dimensional stratified shearing-box magneto-hydrodynamic (MHD) simulations on the gas dynamics of protoplanetary disks with a net vertical magnetic flux of Bz0. All three non-ideal MHD effects, Ohmic resistivity, the Hall effect, and ambipolar diffusion, are included in a self-consistent manner based on equilibrium chemistry. We focus on regions toward outer disk radii, from 5 to 60 AU, where Ohmic resistivity tends to become negligible, ambipolar diffusion dominates over an extended region across the disk height, and the Hall effect largely controls the dynamics near the disk mid-plane. Overall, the basic picture is analogous to the conventional layered accretion scenario applied to the outer disk. In addition, we find that the vertical magnetic flux is strongly concentrated into thin, azimuthally extended shells in most of our simulations beyond 15 AU, leading to enhanced radial density variations know as zonal flows. Theoretical implications and observational consequences are briefly discussed.